Biogenic synthesis of silver nanoparticles from waste banana plant stems and their antibacterial activity against Escherichia coli and Staphylococcus Epidermis - Dang, Huu; Fawcett, Derek; Poinern, Gerrard Eddy Jai (International Journal of Research in Medical Sciences, 2017)
Background: This study for the first time presents an eco-friendly and room temperature procedure for biologically synthesizing silver (Ag) nanoparticles from waste banana plant stems. Methods: A simple and straightforward green chemistry based technique used waste banana plant stems to act as both reducing agent and capping agent to produce Ag nanoparticles, which were subsequently characterized. In addition, antibacterial studies were conducted using the Kirby-Bauer sensitivity method. Results: Advanced characterisation revealed the Ag nanoparticles had a variety of shapes including cubes, truncated triangular and hexagonal plates, and ranged in size from 70 nm up to 600 nm. The gram-negative bacteria Escherichia coli showed the maximum inhibition zone of 12 mm. Conclusions: The study has shown that waste banana plant stems can generate Ag nanoparticles with antibacterial activity against Escherichia coli and Staphylococcus epidermis.